THE COMPARISON OF TOTAL FLAVONOID CONTENT IN RAMANIA (Bouea macrophylla Griffith) BARK AND LEAF EXTRACT USING MACERATION METHOD - Sofyan Erwandi; Irham Taufiqurrahman; Bayu Indra Sukmana (FKG Unlam, 2018)
Background: The wound is defined as a disorder of the functional anatomical structure on the human body. Traditional medicines, specifically herbs, have been used for a long time and used for the research on wound healing process. There are many medicinal plants that can be used to accelerate wound healing, such as Ramania (Bouea macrophylla Griffith). Ramania has numerous contents and one of them is flavonoid that functions as antibacterial and antioxidant. Flavonoids are able to accelerate the growth of new cells and stimulate the fibroblasts formation, thus accelerating the wound healing process. The result of flavonoid compound extraction is influenced by many factors such as part of the plant, solvent and method which is used for the extraction. Purpose: To analyze the difference of total flavonoid contents in ramania (Bouea macrophylla Griffith) bark and leaf extract using maceration method with 95% ethanol solvent. Methods: This study used Quasi experimental with pre-experimental design with quantitative testing. The total samples were 32 male marmots, which divided into 2 treatment groups consisted of ramania bark extract group and ramania leaf extract group. Total levels of flavonoids were calculated using a UV-Vis Spectrophotometer. Results: The mean value of total flavonoid in ramania bark extract was 11.14 μg/mg and the leaf extract was 17.15 μg/mg. The Independent T-test showed that there was significant difference between the treatment groups (p<0.05). Conslusion: It can be concluded that the total flavonoid content found in ramania (Bouea macrophylla Griffith) leaf extract is higher than the bark extract.